Abundance and Diversity of Coral Reef Megabenthos in Karimunjawa Islands, Central Java - Wijaya, Aditya Surya; Haryanti, Dwi; Ramadhan, Muhammad Fadhilah; Wijayanti, Diah Permata (Universitas Diponegoro, 2025)
Karimunjawa is an archipelago which has a large coral reef area. However, the human and natural factors that put environmental pressure on coral reef ecosystem in recent years have caused the need to update data on the abundance and diversity of megabenthos in Karimunjawa. Data collection was carried out on 9 islands in Karimunjawa out on 30 September-4 October in 2023. The megabenthos data collection method was carried out using the belt transect method with data collection carried out at the family level in the survey area. The method for collecting data on hard coral cover was underwater photo transect (UPT). Megabenthos data analysis was carried out using Microsoft Excel software Coral Point Count with Excel Extensions (CPCe) software for coral cover analysis. Analysis of megabenthos data also includes ecological indices consisting of the Shannon-Wiener diversity index, Pielou evenness index, and dominance index. The relationship between hard coral cover and megabenthos was sought using simple regression analysis. The research results found 8 megabenthos classes and as many as 16 families. The results showed a weak relationship between megabenthos abundance and hard coral cover (r=0.03), but a strong and moderate relationship with the megabenthos ecological index (r=0.434 to 0.568). The regression analysis showed that there was no significant influence between hard coral cover and the abundance and ecological index of megabenthos (P>0.05).